Accidents preventive practice for high-rise construction - Abd Rahman, N.; Goh, Kai Chen; Goh, Hui Hwang; Omar, Mohd Faizal; Toh, Tien Choon; Mohd Zin, Abdullah Asuhaimi; Mohd Jaini, Z.; Yunus, R.; Rahmat, S.N. (EDP Sciences, 2016)
The demand of high-rise projects continues to grow due to the reducing of usable land area in Klang Valley, Malaysia.The rapidly development of high-rise projects has leaded to the rise of fatalities and accidents.An accident that happened in a construction site can cause serious physical injury.The accidents such as people falling from height and struck by falling object were the most frequent accidents happened in Malaysian construction industry.The continuous growth of high-rise buildings indicates that there is a need of an effective safety and health management. Hence, this research aims to identify the causes of accidents and the ways to prevent accidents that occur at high-rise building construction site.Qualitative method was employed in this research. Interview surveying with safety officers who are involved in highrise building project in Kuala Lumpur were conducted in this research. Accidents were caused by man-made factors, environment factors or machinery factors.The accidents prevention methods were provide sufficient Personal Protective Equipment (PPE), have a good housekeeping, execute safety inspection, provide safety training and execute accidents investigation.In the meanwhile, interviewees have suggested the new prevention methods that were develop a proper site layout planning and de-merit and merit system among subcontractors, suppliers and even employees regarding safety at workplace matters.This research helps in explaining the causes of accidents and identifying area where prevention action should be implemented, so that workers and top management will increase awareness in preventing site accidents.